2010
DOI: 10.5483/bmbrep.2010.43.8.561
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of HIV-1 Tat fusion protein transduction efficiency by bog blueberry anthocyanins

Abstract: Though protein transduction domains (PTDs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Particularly, superoxide dismutase (SOD) catalyzes peroxidation of numerous harmful free radicals; thus, providing ample cellular protection against oxidative damage (8). We previously reported that anti-oxidant enzymes such as SOD, ribosomal protein S3, and sensitive to apoptosis gene fused with PTD and the fusion proteins are effectively delivered to cells and tissues and exert protection against inflammation, ischemia, and Parkinson's disease (9-11) Additionally, bog blueberry anthocyanins and levosulpiride enhance transduction efficiency of PTD-fused proteins into cells and have the ability to significantly improve the therapeutic potential of PTD-fused proteins (12,13). In the present study, we investigated whether silk fibroin peptide could affect the in vitro and in vivo transduction efficiency of Tat-SOD into HaCaT cells and mice skin.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, superoxide dismutase (SOD) catalyzes peroxidation of numerous harmful free radicals; thus, providing ample cellular protection against oxidative damage (8). We previously reported that anti-oxidant enzymes such as SOD, ribosomal protein S3, and sensitive to apoptosis gene fused with PTD and the fusion proteins are effectively delivered to cells and tissues and exert protection against inflammation, ischemia, and Parkinson's disease (9-11) Additionally, bog blueberry anthocyanins and levosulpiride enhance transduction efficiency of PTD-fused proteins into cells and have the ability to significantly improve the therapeutic potential of PTD-fused proteins (12,13). In the present study, we investigated whether silk fibroin peptide could affect the in vitro and in vivo transduction efficiency of Tat-SOD into HaCaT cells and mice skin.…”
Section: Introductionmentioning
confidence: 99%
“…Recently it was reported that treatment with 10% DMSO can facilitate the transduction of PTD fused proteins into cells (23). Also, we showed that bog blueberry anthocyanins (BBA) enhance the transduction efficiency of Tat-SOD into Hela cells and mice skin (24). Previously we reported that PEP-1-CAT proteins are significantly transduced into astrocytes in time-and dose-dependent manner and exert protective activity against ischemic neuronal damage (5).…”
Section: Effect Of Imipramine On Transduction Efficiency Of Pep-1-catmentioning
confidence: 99%
“…Several small regions of proteins, called protein transduction domains (PTDs), have been developed to allow the delivery of exogenous proteins into living cells. In a previous study, we used this technology to show that various fusion proteins efficiently protect against cell death in vitro and in vivo (15)(16)(17)(18)(19)(20). In the present study, we examined the inhibitory effects of Tat-ANX1 protein against LPS-induced inflammation-associated gene expression in murin macrophage Raw 264.7 cells.…”
Section: Introductionmentioning
confidence: 99%
“…PTD can deliver exogenous target proteins into cells regardless of protein size and thus has been developed for therapeutic applications (22). Previously, we extensively studied PTD fusion proteins in vitro and in vivo and showed them to be beneficial in several diseases such as inflammation, Parkinson's disease, diabetes, and ischemia (15)(16)(17)(18)(19)(20).…”
Section: Figmentioning
confidence: 99%